Facing death. Student’s thoughts towards the feeling of their own death. - Martí-García, Celia; Fernández-Alcántara, Manuel; Ruiz-Martín, Laura; Montoya-Juárez, Rafael; Hueso-Montoro, Cesar; García-Caro, M Paz (Anales de Psicología / Annals of Psychology, 2017)
Narratives produced by thinking and reflecting about death and dying may be themselves a source of new knowledge in the study of anxiety and attitudes toward death. A qualitative descriptive study aimed to explore the features of thoughts, emotions and feelings about young people’s own death, (nursing students) was conducted. 85 students voluntarily answered a self-administered questionnaire with open questions based on Mortality Salience, used in the Terror Management Theory. Content analysis using Atlas.ti software was performed. When reflecting upon their own death, participants reported substantive emotions such as fear, pain, distress, sadness or loneliness. The fear of their own death was specified as the inability to achieve goals in life, to leave the family and the dying process itself. When reflecting upon been physically dead, attributes of the decomposition of the body, spiritual attributes, beliefs, denial and preferences were identified. Cultural worldview, values and beliefs of each person were remarkably present when thinking about their own death.